When Leadership Goes Unnoticed: The Moderating Role of Follower Self-Esteem on the Relationship Between Ethical Leadership and Follower Behavior - Avey, James B. (Journal of business ethics, 2011)
The authors examined the effects of ethical leadership on follower organizational citizenship behavior (OCB) and deviant behavior. Drawing upon research related to the behavioral plasticity hypothesis, the authors examined a moderating role of follower self- esteem in these relationships. Results from a field study revealed that ethical leadership is positively related to follower OCB and negatively related to deviance. We found that these relationships are moderated by followers’ self-esteem, such that the relationships between ethical leadership and OCB as well as between ethical leadership and deviant behavior are weaker when followers’ self-esteem is high than low. Implications of these findings for research and practice are discussed.